The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1186/s13756-021-00898-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coronavirus disease 2019 (COVID-19) pandemic on antimicrobial prevalence and prescribing in a tertiary hospital in Singapore

Abstract: Background The deployment of antimicrobial stewardship (AMS) teams to deal with the COVID-19 pandemic can lead to a loss of developed frameworks, best practices and leadership resulting in adverse impact on antimicrobial prescribing and resistance. We aim to investigate effects of reduction in AMS resources during the COVID-19 pandemic on antimicrobial prescribing. Methods One of 5 full-time equivalent AMS pharmacists was deployed to support pandem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 15 publications
1
30
0
1
Order By: Relevance
“…In China, the influence factors and their interaction relation of antibiotics use under the COVID-19 pandemic were becoming clear ( Figure 7 ). The shock of COVID-19 in 2020 led to significant decline in antibiotic consumption around the world ( Swedres-Svarm, 2020 ; Blix and Høye, 2021 ; Buehrle et al, 2021 ; ECDC, 2021 ; Gagliotti et al, 2021 ; Hogberg et al, 2021 ; King et al, 2021 ; Ng et al, 2021 ; Penalva et al, 2021 ; Sundhedsdatastyrelsen, 2021 ), and China is no exception. The decreases of antibiotic consumption during the COVID-19 pandemic might be due to the declined infectious diseases incidence caused by non-pharmaceutical interventions (NPIs) introduced to reduce COVID-19 transmission ( Swedres-Svarm, 2020 ; Gagliotti et al, 2021 ; Penalva et al, 2021 ; Ullrich et al, 2021 ), as well as the reduction of medical service contact and the compression of irrational prescriptions during the pandemic lockdown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In China, the influence factors and their interaction relation of antibiotics use under the COVID-19 pandemic were becoming clear ( Figure 7 ). The shock of COVID-19 in 2020 led to significant decline in antibiotic consumption around the world ( Swedres-Svarm, 2020 ; Blix and Høye, 2021 ; Buehrle et al, 2021 ; ECDC, 2021 ; Gagliotti et al, 2021 ; Hogberg et al, 2021 ; King et al, 2021 ; Ng et al, 2021 ; Penalva et al, 2021 ; Sundhedsdatastyrelsen, 2021 ), and China is no exception. The decreases of antibiotic consumption during the COVID-19 pandemic might be due to the declined infectious diseases incidence caused by non-pharmaceutical interventions (NPIs) introduced to reduce COVID-19 transmission ( Swedres-Svarm, 2020 ; Gagliotti et al, 2021 ; Penalva et al, 2021 ; Ullrich et al, 2021 ), as well as the reduction of medical service contact and the compression of irrational prescriptions during the pandemic lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…The generalized linear model (GLM) was used to examine the change of health facilities’ antibiotic consumption under the impact of the COVID-19 pandemic. According to previous studies, the impact of the COVID-19 pandemic on the use of antibiotics in medical institutions might be related to the drug treatment of COVID-19 cases ( Li et al, 2020 ; Langford et al, 2021 ) and the decline of medical services due to COVID-19 control measures ( Buehrle et al, 2021 ; ECDC, 2021 ; Hogberg et al, 2021 ; King et al, 2021 ; Ng et al, 2021 ). Thus, two variables (medical service decline and number of COVID-19 cases under treatment) were selected as the indirect measures of the COVID-19 pandemic to estimate the change of antibiotic use at the population level.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore antimicrobial monitoring use in the case of the pandemic is crucial to identify concerning signs of misuse or overuse. Studies conducted in several countries found an increase in antimicrobial consumption in ICUs during the pandemic (Guisado-Gil et al, 2020;Rawson et al, 2020;Grau et al, 2021b;Ng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%